Measurement of neurofilaments improves stratification of future disease activity in early multiple sclerosis - Uher, Tomas; Havrdova, Eva Kubala; Benkert, Pascal; Bergsland, Niels; Krasensky, Jan; Srpova, Barbora; Dwyer, Michael; Tyblova, Michaela; Meier, Stephanie; Vaneckova, Manuela; Horakova, Dana; Zivadinov, Robert; et al. (Multiple sclerosis (Houndmills, Basingstoke, England), 2021)
BACKGROUND: The added value of neurofilament light chain levels in serum (sNfL) to the concept of no evidence of disease activity-3 (NEDA-3) has not yet been investigated in detail. OBJECTIVE: To assess whether combination of sNfL with NEDA-3 status improves identification of patients at higher risk of disease activity during the following year. METHODS: We analyzed 369 blood samples from 155 early relapsing-remitting MS patients on interferon beta-1a. We compared disease activity, including the rate of brain volume loss in subgroups defined by NEDA-3 status and high or low sNfL (> 90th or < 90th percentile). RESULTS: In patients with disease activity (EDA-3), those with higher sNFL had higher odds of EDA-3 in the following year than those with low sNFL (86.5% vs 57.9%; OR = 4.25, 95% CI: [2.02, 8.95]; p = 0.0001) and greater whole brain volume loss during the following year (β = -0.36%; 95% CI = [-0.60, -0.13]; p = 0.002). Accordingly, NEDA-3 patients with high sNfL showed numerically higher disease activity (EDA-3) in the following year compared with those with low sNfL (57.1% vs 31.1%). CONCLUSION: sNfL improves the ability to identify patients at higher risk of future disease activity, beyond their NEDA-3 status. Measurement of sNfL may assist clinicians in decision-making by providing more sensitive prognostic information.
Keywords: multiple sclerosis; Intermediate Filaments; intermediární filamenta; mozek; lidé; Multiple Sclerosis; MRI; NEDA-3; brain atrophy; Brain; Neuroﬁlament light chain; roztroušená skleróza; Neurofilament Proteins; neurofilamentové proteiny; Humans